Prolonged Trachyte Storage and Unusual Remobilization at Piton de la Fournaise, La Réunion Island, Indian Ocean: Li, O, Sr, Nd, Pb and Th Isotope Study. (28th May 2021) - Vlastelic, I; Bachèlery, P; Sigmarsson, O; Koga, K T; Rose-Koga, E R; Bindeman, I; Gannoun, A; Devidal, J -L; Falco, G; Staudacher, T
Abstract: La Réunion Island includes two major volcanic systems. About 0·5 Myr ago, Piton des Neiges volcano declined, while Piton de la Fournaise volcano grew on its flank. Since then the Piton de la Fournaise shield volcano has produced homogeneous lavas with chemical compositions transitional between alkali and tholeiitic basalts. In April 2007, the volcano emitted a very small volume of trachytic pumice during its largest historical eruption. We conducted a comprehensive petrological and geochemical study of the pumice to understand the occurrence of such silicic melt in the feeding system of this highly active basaltic volcano. Isotopes of Sr, Nd, Pb and O, together with trace elements, indicate that the trachyte is genetically related to the La Réunion mantle plume and derives from crystallization of a typical basalt. The trachyte chemistry records a long and complex history of differentiation and outgassing. The extensive depletion of moderately volatile elements (F, Cl, B, Cs, Cu, Li) and less volatile uranium is consistent with exsolution of dense fluids at depths of several kilometres. Lithium isotopes point to closed-system degassing during the very late stages of crystallization. U-series isotopes and radiogenic 208 Pb*/ 206 Pb* constrain the age of U loss to between 0·4 and 2·1 Ma. This age is as old as or older than the Piton de la Fournaise shield edifice. The 2007 trachyte could thus be a liquid remnant of an extinct volcano, such as Piton des Neiges or Les Alizés (Piton de la Fournaise proto-volcano). It could also result from partial melting of an old syenite intrusion or remobilization of interstitial melts not fully solidified. Thermal modelling indicates that the sustained heat flux from hot basaltic magmas rising from the mantle can maintain temperatures above 800 °C in the central feeding system, and prevent total solidification of magmas trapped in this hot core.